Recreational swimming as a physical aspect of wellness and its impact on health tourism - Nićiforović, Jovan; Stajić, Dalibor (Hotel and Tourism Management, 2021)
Changes in Fitness indexvalues, monitored by the Urho Kaleva Kekkonen (UKK) Walking test, were examined in this study due to its practical application in the assessment of aerobic capacity, especially after planned wellness activities of moderate intensity. This research is designed as a quasi-experimental uncontrolled before and after study, and according to it, Fitness index values obtained by the UKK test and body mass index (BMI) were evaluated before and after 8 weeks of planned wellness activities (recreational swimming). After the wellness activity, the average Fitness index value was increased by 1.13% (the difference was statistically significant with p = 0.000) while BMI value was significantly decreased by 1.82% (p = 0.000). Considering our results, the Fitness index could have practical importance for the assessment of endurance performance in man. That means that Fitness index can be used for estimating aerobic capacity and effect of wellness on health improvement and disease prevention.